L’expérience Soho Solo dans le Gers : exemple d’une campagne innovante ? - Patricia Sajous (Netcom)
This paper aims to describe an innovative country profile based on the study of the Soho Solo experience conducted in the department of Gers since 2001. This local development plan supports the setting up of teleworkers and their families. Public players’ objectives, uses of internet based on local opportunities concerning technology and public funds improve an original concept which can be developed only in the rural society. In order to talk about this concept as an innovative concept, we have analyzed features of teleworkers interested in and the first special effects.